Bajcsy-Zsilinszky Endre, Ambrus Zoltán, József Attila, Kosztolányi Dezső levelei B. Gy. másolataiban és kommentárjaival - Bajcsy-Zsilinszky Endre, Ambrus Zoltán, József Attila, Kosztolányi Dezső, B. Gy. (Fond 7 Magyar Szemle Társaság)
Fond 7 Magyar Szemle Társaság > II. rész